Reflective journal writing of undergraduate students enrolled in sex education in Hong Kong. Issue 5 (3rd September 2018) - Or, Peggy
ABSTRACT: The purpose of this study was to investigate the impact of reflective journal writing on the thinking process and academic performance of local undergraduates in their course on sexual health and human sexuality. A two-group quasi-experimental design was used to analyze students' reflective journals in terms of learning gains on sex education. The data for analysis were extracted from the 159 specific phrases which were categorized and retrieved through NVivo analysis of the students' reflective journals. The comments about thinking were the largest number of responses. The correlation between academic performance and self-reflection was significant; the F value (0.125, 0.025) = 4.96, p value was 0.029 which is significant at p < 0.05. There is a relationship between reflection and course grade in the context of sex education.